Using in vitro derived enzymatic reaction rates of metabolism to inform pesticide body burdens in amphibians. (15th May 2018) - Glinski, Donna A.; Henderson, W. Matthew; Van Meter, Robin J.; Purucker, S. Thomas
Graphical abstract: Highlights: Exposed microsomes and live toads to broad-spectrum pesticides. Enzymatic reaction rates of pesticides were calculated in amphibian liver microsomes. Intrinsic clearance rates from in vivo exposures were estimated for these pesticides. In vitro to in vivo derived parameters suggest blood flow limited metabolism. Abstract: Understanding how pesticide exposure to non-target species influences toxicity is necessary to accurately assess the ecological risks these compounds pose. To assess the potential metabolic activation of broad use pesticides in amphibians, in vitro and in vivo metabolic rate constants were derived from toad ( Anaxyrus terrestris ) livers in experiments measuring the depletion of atrazine (ATZ), triadimefon (TDN), and fipronil (FIP) as well as formation of their metabolites. To determine the predictability of these in vitro derived rate constants, Fowler's toads ( Anaxyrus fowleri ) were exposed to soil contaminated with each of the pesticides at maximum application rate. Desethyl atrazine (DEA) and deisopropyl atrazine (DIA), both metabolites of ATZ, exhibited similar velocities (Vmax ) while the KM constant for DIA was two times higher than DEA. TDN was metabolized into two diastereomers of triadimenol (TDL A and TDL B), where TDL B had a Vmax around two times higher than TDL A. The metabolite fipronil sulfone's Vmax and KM were 150 pmol min −1  mg −1 and 29 μM, respectively. While intrinsic clearance rates for the pesticides ranged from 0.54 to 38.31 mL min −1  kg −1 . Thus, gaining knowledge on differences in metabolism of pesticides within amphibians is important in estimating risk to these non-target species since the inherent toxicity of metabolites can differ from the parent compound.